Hydration-dehydration Treatments for Improved Seed Storability of Bamboo (Dendrocalamus strictus L.) - Sur, Kalpana; Lahiri, A. K.; Basu, R. N. (Indian Forester, 1988)
Soaking of bamboo seeds (Dendrocalamus Strictus L.) in water or a dilute solution of disodium hydrogen phosphate (l0-1M) for 6 hr, followed in either case by drying back, greatly reduced their deterioration under accelerated ageing at 92% RH and 40Â°C for 5 days. Hydration by moisture equilibration with a water saturated atmosphere for 48 hr followed by drying also slowed down the loss of vigour and viability of seeds. Soaking-drying treatment was, however, more effective than the moisture equilibration-drying treatment. Although the soaking-drying treatment with low concentratlon of disodium hydrogen phosphate (10-4M) proved better than water (SD) for maintaining vigour and viabilily, GA treatment showed better seedling growth (not germination percentage) than the other treatments. Kinetin and ethephon adversely affected post-storage germinability.